2020
DOI: 10.1111/php.13358
|View full text |Cite
|
Sign up to set email alerts
|

Combined Addition of Ethanol and Ethylenediaminetetraacetic Acid Enhances Antibacterial and Antibiofilm Effects in Methylene Blue‐Mediated Photodynamic Treatment against Pseudomonas aeruginosa In Vitro

Abstract: Antimicrobial photodynamic treatment (aPDT) for infection with drug-resistant bacteria has received much attention. For P. aeruginosa, however, efficient formation of biofilms and the nature of Gram-negative bacteria often limit the efficacy of aPDT. In this study, we investigated the effects of ethanol and ethylenediaminetetraacetic acid (EDTA) as additives on bacterial viability, biofilm biomass, and structures of bacteria and biofilms in methylene blue (MB)-mediated aPDT in vitro. Matured P. aeruginosa biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…Most PSs used were of phenothiazinium-based dyes, including MB, Rose Bengal (RB), and toluene blue O (TBO). Similar to our study yet using one concentration of MB coupled with variable fluences and step ranges of red light against a wide range of global priority drug-resistant bacteria including ESKAPE pathogens and two yeast species, Candida albicans and Cryptococcus neoformans, Sabino CP et al St Denis et al, 2013;Sarker et al, 2021) successfully demonstrated the efficacy of MB-aPDT against across all the selected strains in species-specific dose-response kinetics regardless of drug-resistance profiles. The improvement of the efficacy of MB-aPDT was observed with the addition of some chemical compounds (Vecchio et al, 2015) including an inert inorganic salt potassium iodide (KI) (Vecchio et al, 2015), which seems to be safe for future clinical application.…”
Section: <0001supporting
confidence: 78%
“…Most PSs used were of phenothiazinium-based dyes, including MB, Rose Bengal (RB), and toluene blue O (TBO). Similar to our study yet using one concentration of MB coupled with variable fluences and step ranges of red light against a wide range of global priority drug-resistant bacteria including ESKAPE pathogens and two yeast species, Candida albicans and Cryptococcus neoformans, Sabino CP et al St Denis et al, 2013;Sarker et al, 2021) successfully demonstrated the efficacy of MB-aPDT against across all the selected strains in species-specific dose-response kinetics regardless of drug-resistance profiles. The improvement of the efficacy of MB-aPDT was observed with the addition of some chemical compounds (Vecchio et al, 2015) including an inert inorganic salt potassium iodide (KI) (Vecchio et al, 2015), which seems to be safe for future clinical application.…”
Section: <0001supporting
confidence: 78%
“…We previously showed that MB-mediated aPDT effectively killed P. aeruginosa in mature biofilms when ethanol and EDTA were added to the PS mixture in vitro . 13 In addition, MB-mediated aPDT with the addition of ethanol, EDTA, and DMSO for 7 consecutive days suppressed bacterial invasion from the wound to the inside of the rats with a P. aeruginosa -infected, extended, full-thickness burn. 5 However, some rats under this treatment showed certain bacterial invasion, and the rescue rate was limited to 78.6% (11 out of 14 rats).…”
Section: Discussionmentioning
confidence: 96%
“…The concentrations of ethanol, at 10%, and EDTA, at 10 mM, were based on the results of our previous in vitro study on the aPDT against P. aeruginosa in biofilms. 13 Meanwhile, the concentration of DMSO was determined based on the observation that 25% DMSO displayed no dark toxicity on the bacteria in the biofilm in vitro (data not shown). Here, we compared the efficacies of aPDT with only MB; aPDT with MB, EDTA, and ethanol (MB/EDTA/ethanol); and aPDT with MB, EDTA, ethanol, and DMSO (MB/EDTA/ethanol/DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…In an in vitro experiment, we found that MB with the addition of both EDTA and ethanol significantly improved bactericidal effects when compared with MB alone, MB with only EDTA, or MB with only ethanol. We also observed that the biofilm biomass was reduced by the addition of EDTA [16]. In an in vivo experiment, the addition of DMSO effectively reduced bacterial numbers in the deep tissue region.…”
Section: Ps Mixture and In Vitro Dark Toxicitymentioning
confidence: 55%